Côte d’Ivoire - Public Expenditure Management and Financial Accountability Review : Volume 1. Main Report - World Bank (Washington, DC, 2012)
This review was conducted in Cote d'Ivoire with the goal of establishing the reference situation of the management and system of public finances, including procurement, and facilitating the monitoring of the impact of the reforms to improve the management and efficiency of public policies and their fiduciary framework. The review presents three in-depth analyses. After summarizing the main conclusions and recommendations of the priority measures, the review presents the results of the following analyses: i) public expenditure review, which analyses recent macro-economic and fiscal developments in relation to the budget execution and Cote d'Ivoire's poverty reduction strategy; ii) review of the public financial management system, conducted on the basis of the findings of the "Public Financial Management Performance Report" (PFM PR), which constitutes volume two of this review. The PFM PR was prepared using the "Public Financial Management Performance Measurement Framework" established in the context of the partnership under the "Public Expenditure and Financial Accountability" (PEFA) program; and iii) review of the public procurement system prepared on the basis of findings of the "Public Procurement Assessment Report". This report, which constitutes three volumes of this review, was prepared according to the methodology for assessment of national procurement systems approved by the Organization of Economic Cooperation and Development (OECD's) Development Assistance Committee (DAC). At the end of each review, the report proposes an exhaustive action plan of corrective measures for enhancing the efficiency and transparency in the use of government resources and improving the public finance management system and the quality of procurement.